The effect of epinephrine and other agents on adenyl cyclase in the cell membrane of avian erythrocytes - Øye, Ivar; Sutherland, Earl W. (Biochimica et biophysica acta, 1966)
1. 1. Cell membranes were prepared from turkey erythrocytes by fragmentation into small particles or larger pieces. Extensively fragmented bits of membrane did not respond to addition of epinphrine while larger pieces did respond to epinephrine. 2. 2. Aging of cell membrane preparations in the cold led to a loss of responsiveness to epinephrine. The responsiveness could be restored by prior incubation with a sulfhydryl reagent such as mercaptoethanol. 3. 3. ATP and magnesium ions applied to the exterior of intact erythrocytes did not cause synthesis of adenosine 3′,5′-phosphate. Several proteolytic enzymes were unable to inactivate adenyl cyclase when applied to intact cells but did inactivate the adenyl cyclase of hemolyzed preparations. 4. 4. The ATPase activity of the cells was apparent when ATP was added to intact erythrocytes. Some of the ATPase activity was lost when proteolytic enzymes were added to intact cells but most ATPase activity was retained unless the cells were first hemolyzed before addition of the enzymez.